THE POTENCIAL OF GINGER (ZINGIBER OFFICINALE R.) AS A STANDARDIZED HERBAL PRODUCT IN NORTH SUMATERA - Siregar, Rahmad Syukur; Hadiguna, Rika Ampuh; Kamil, Insannul; Nazir, Novizar; Nofialdi, Nofialdi (UI Scholars Hub, 2022)
Indonesia has more than 9,609 plant species which have medicinal properties that is spread across various regions in Indonesia. Ginger is a group of medicinal plants that are therapeutic. Ginger has been cultivated on a large scale with the highest harvested area, total production and demand in Indonesia, including the Province of North Sumatra. The use of ginger as a medicinal plant has been carried out on the scale of the Traditional Medicine Industry (IOT), of which there are 135 IOTs in Indonesia and one of them is in North Sumatra, namely in the city of Medan. This article uses the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) method by identifying articles from various scientific report source databases, Pubmed, Scopus, Science Direct and Elsevier. The selection of articles is taken from the period between 2019-2022, 38 out of 100 articles and reports have been included in the criteria. From the studies that have been conducted, it can be concluded that the existence of IOT supported by tools and technology as well as policies that can protect the standardized herbal medicine agro-industry which will be the driving force for the ginger agro-industry so that it can meet the demand for domestic medicinal materials, increase export share, as well as be able to compete in the global market.